Can Energy Consumption and Benefit Programs Explain One's Living Standards Afterwards? Evidence from Northern Sulawesi, Indonesia - Tasik, Hizkia H. D. (International Journal of Energy Economics and Policy, 2020)
The Indonesian government has been serious in alleviating poverty in Indonesia through the implementation of public benefit programs including alterations in energy subsidy program. Generally, the poverty rate has finally reached a single digit. On the other hand, the Human Development Index as one indicator of living standard has not shown improvement as fast as the improvement in the poverty rate. A question remains. After all benefit programs are in effect, are the living standards of people improving? This study relies on a survey covering 315 respondents residing in North Sulawesi Province, Indonesia. Ordinary least square and ordered logistics models are used to analyze the survey data. The findings suggest that spending on electricity reduces the ability to meet daily needs but not necessarily makes lives better or worse. BPJS health insurance holders tend to have a lower rate of better living after benefit programs take place as compared to non-holders. Additionally, being the holder does not statistically affect the ability to meet daily needs. Having good academic ranks in high school is associated with having better lives. In contrast, having these ranks tend to reduce the ability to meet daily needs. Keywords: Energy Consumption; Better Lives; Daily Needs; Living Standards JEL Classifications: O1, Q48, I32, H53 DOI: https://doi.org/10.32479/ijeep.9208